UPAYA KOREA SELATAN MENGEMBALIKAN STATUS MITRA DAGANG PRIORITAS YANG DICABUT JEPANG PADA TAHUN 2019 - Dharma Putra, I Putu Andre; Kumala Dewi, Putu Ratih; Parameswari, A.A Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
This research describes South Korea's efforts to restore the status of a priority trading partner that Japan revoked in 2019. The relationship between the two countries is not good, but South Korea and Japan agreed to normalize through economic cooperation. South Korea and Japan are two advanced technology producing countries that carry out various collaborations to improve the national economy. South Korea is one of the countries given priority trading partner status by Japan to accelerate the economic wheels of the two countries. South Korea uses this status to import fluorinated polyamide, photosensitizing agent resist, and high purity hydrogen fluoride to produce advanced technology such as cellphones and televisions. In 2019, Japan revoked the status of a priority trading partner because of a conflict that threatened the flow of South Korean technology production. Keywords: Priority Trade Partners, Technology Industry, Economic Cooperation, Coercive Diplomacy.